Sexual disorders among temporal lobe epilepsy patients preand post-surgery - D. G. Shefer; A. S. Shershever; V. B. Boreyko; A. V. Klein; E. V. Sorokova (Эпилепсия и пароксизмальные состояния, 2023)
Objective: to investigate sexual disorders (SDs) in patients with temporal lobe epilepsy (TLE) both before and after undergoing various temporal lobe operative procedures.Material and methods. A retrospective andrological and sexologic study was conducted, utilizing catamnesis data. Multiple examination methods were employed, including semen and prostatic fluid analysis, Decourt–Dumic sperm morphotype analysis, vegetative tests, Shcherbak thermoregulation reflex examination, ultraviolet erythema test, sugar curve analysis, and electroencephalography. The study assessed the results of surgical treatment and long-term catamnesis for 120 TLE patients who had undergone various temporal lobe operative procedures (TLPs), with ages at the time of surgery ranging from 4.5 to 47 years. Among them, 82 patients (41 males and 41 females) in the main group reported complaints of SDs, representing 100% for all calculations.Results. Hypersexuality and sexual perversions were most prevalent among patients with severe mental disorders. Following TLPs, patients with mild mental disorders and cessation of epileptic seizures (EPs) experienced regression in 83.6% of SD cases. Conversely, among patients with severe mental disorders, SDs regressed in 45% of cases after TLPs. Encouraging outcomes were observed in patients with hypersexuality, which was ameliorated after the cessation of EPs, with a catamnesis period ranging from 17 to 24 years.Conclusion. This study, conducted in real-world clinical settings, supports the recommendation of surgical treatment for TLE patients with mild mental disorders. In the majority of cases, the cessation or reduction of EPs following TLPs leads to improvements in TLE manifestations, including the patient's mental state, SDs, and social adaptation.